1995
DOI: 10.1093/gerona/50a.1.m7
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Exercise Training in Older Coronary Patients

Abstract: While spontaneous improvements in peak oxygen consumption are seen in older coronary patients in the months following a coronary event, a formal exercise training program results in significantly greater increases in peak exercise capacity and in peak and submaximal exercise efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 0 publications
2
30
1
3
Order By: Relevance
“…7 Compared with several previous studies performed in other countries, 7,[19][20][21] in the present study oxygen consumption was already at higher levels at baseline, which may be why no significant improvement in peak V…”
Section: Physical Fitnesscontrasting
confidence: 77%
See 2 more Smart Citations
“…7 Compared with several previous studies performed in other countries, 7,[19][20][21] in the present study oxygen consumption was already at higher levels at baseline, which may be why no significant improvement in peak V…”
Section: Physical Fitnesscontrasting
confidence: 77%
“…17,18 Previous studies of elderly participants have indicated a diminished exercise capacity compared with younger subjects; however, similar improvements in aerobic capacity have been observed after exercise training. 19 Ades and Grunvald demonstrated that elderly patients were usually substantially less fit; however, they obtained greater improvements in their aerobic capacity as shown by enhanced peak oxygen consumption and duration of treadmill exercise after cardiac rehabilitation. 20 On the other hand, Lavie et al reported that improvements in cardiopulmonary variables, such as peak V…”
Section: Physical Fitnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Enrolment rates for Cardiac Rehabilitation have been reported to range from 15-59% [19]. Many services concentrate on relatively low risk, white middle aged patients, while women [20,21] and elderly are less likely to be included [22][23][24]. Poor recruitment is also related to service factors, such as the availability and accessibility of a program [25], the strength of a physician's recommendation to attend [26][27][28] and treatment by a general physician, rather than a cardiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients with CAD have exercise trainability comparable to that of younger patients participating in similar exercise rehabilitation, with elderly male and female patients showing comparable improvement. [45][46][47] However, referral to and participation in exercise rehabilitation is less frequent for older patients, especially for older women. 48 No significant complications or adverse outcomes of exercise training in older patients have been described in any study.…”
Section: Exercise Training For Older Patients With Cadmentioning
confidence: 99%